The study of the efficacy of multipurpose solutions to inhibit bacteria on soft contact lens - ทองวิเศษสุข, ธีรภัทร; สินปรุ, เบญญา; หลำใจซื่อ, ภัทรชนก; จำรูญ, นพดล (Disease Control Journal, 2018)
A contact lens is the most commonly used medical device for visual correction. However, the incidence of contact lens contamination and contact lens-related microbial keratitis remain a health problem. Thus, various types of multipurpose solutions have been developed for cleaning a used contact lens. The aim of this study is to test the efficacy of three multipurpose solutions brands (A, B and C) in terms of their efficacy to inhibit the growth of Pseudomonas aeruginosa ATCC 25923 and Staphylococcus aureus ATCC 25923 contaminated on a soft contact lens. In this study, the solutions A and C, which contain the same ingredients (i.e. boric acid, polidronium chloride 0.001%, myristamidopropyl dimethylamine 0.0005%), and the solution B, which consists of boric acid, sodium borate, polyaminopropyl biguanide 0.00013%, polyquaternium 0.0001% were found to have demonstrated the optimum temperature and incubation time for inhibiting the growth of bacteria. A bacterial cell concentration of as 1.5X106 CFU/ml was selected to prepare a soft contact lens bacterial contamination model. All the three solutions could inhibit the growth of P. aeruginosa ATCC 25923 and S. aureus ATCC 25923 based on the indications on the medication information leaflet of each product. As a result, the solutions A, B and C could inhibit S. aureus from 2 hours to 28 days at 6±2˚C, 25±2˚C and 35±2˚C. Both A and C solutions could inhibit P. aeruginosa from 2 hours to 28 days at all temperatures studied. The solution B could inhibit P. Aeruginosa from 2 hours to 28 days at 25±2˚C but <24 hours at 6±2˚C and <4 hours at 35±2˚C, the colonies of P. aeruginosa were still found under these conditions. Findings from this study could be used as the guidelines for cleaning and storing a soft contact lens with multipurpose solutions to prevent microbial keratitis from a used contact